SCHOOL - A TOOL OF CONSOLIDATION - Artemenko, О.; Аnzorova, S.; Gasanova, P.; Nikitina, М.; Fedorova, S.; Petrukhina, D. (Scientific Journal of Pedagogy and Economics, 2020)
In modern conditions of the world economy's monopolization, sanctions, the flow of external migration of the labor force is an urgent problem of the necessity at the state level to preserve the cohesion and unity of the multiethnic Russian society. The article examines the historical development of Russia, where the school as a social institution performs not only an educational function but also the role of consolidating the multiethnic composition of the state. Russian language and culture fulfill this role through the school. Russian is historically considered as the language of integration of nations who have passed their ethnoge- nesis on the territory of Russia, their spiritual and cultural rapprochement with the Russians by the method of N. I. Ilminsky while preserving the native languages of students. Performing the function of consolidation, the Russian language acted as an integrator of nations, not their assimilator, as evidenced by statistics on the actual existence of more than 230 languages and dialects of nations. The article notes that in Russian politics before the reconstruction period, the school, performing a conso-lidating function, was a tool for leveling the ethnic characteristics of students, through unitary language training, forming national-Russian bilingualism. The analysis of scientific sources shows that such conditions before the reconstruction period led to objective facts not manifestations of interethnic conflicts. Also, during the entire Soviet period, literary languages were created and developed, and dialects were preserved to some extent, but, unfortunately, the functions of native languages were narrowed in social spheres. Describing the post-soviet period, cultural and linguistic diversity is noted, which is a significant source of social conflicts and political discussions. Under these conditions, cultural and linguistic state homogeneity becomes a subject of dissatisfaction in the public life of speakers of minority languages. The problem arises as to how to guarantee the participation of each language group in the life of a multilingual society with their socio-cultural integration, without violating international human rights legislation.